![image](https://tex.z-dn.net/?f=+A+%3E+0+%5C+%2C+)
0 \ , " alt=" A > 0 \ , " align="absmiddle" class="latex-formula"> причём
![image](https://tex.z-dn.net/?f=+A+%3E+%5Cfrac%7B1%7D%7BA%7D+%5C+%3B+%5C+%5CRightarrow+%5C+%5C+A%5E2+%3E+1+%5C+%3B+%5C+%5CRightarrow+%5C+%5C+A+%3E+1+%5C+%3B+)
\frac{1}{A} \ ; \ \Rightarrow \ \ A^2 > 1 \ ; \ \Rightarrow \ \ A > 1 \ ; " alt=" A > \frac{1}{A} \ ; \ \Rightarrow \ \ A^2 > 1 \ ; \ \Rightarrow \ \ A > 1 \ ; " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+A+%3E+a+%3E+%5Cfrac%7B1%7D%7BA%7D+%3E+0+%5C+%3B+%5C+%5CRightarrow+%5C+%5C+Aa+%3E+1+%5C+%3B+)
a > \frac{1}{A} > 0 \ ; \ \Rightarrow \ \ Aa > 1 \ ; " alt=" A > a > \frac{1}{A} > 0 \ ; \ \Rightarrow \ \ Aa > 1 \ ; " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+B+%3E+0+%5C+%2C+)
0 \ , " alt=" B > 0 \ , " align="absmiddle" class="latex-formula"> причём
![image](https://tex.z-dn.net/?f=+B+%3E+b+%3E+1+%5C+%3B+%5C+%5CRightarrow+%5C+%5C+Bb+%3E+1+%5C+%3B+)
b > 1 \ ; \ \Rightarrow \ \ Bb > 1 \ ; " alt=" B > b > 1 \ ; \ \Rightarrow \ \ Bb > 1 \ ; " align="absmiddle" class="latex-formula">
Рассмотрим три выражения:
![Middle: \ \ \ \ \ M = A + \frac{1}{Ab} + b \ Middle: \ \ \ \ \ M = A + \frac{1}{Ab} + b \](https://tex.z-dn.net/?f=+Middle%3A+%5C+%5C+%5C+%5C+%5C+M+%3D+A+%2B+%5Cfrac%7B1%7D%7BAb%7D+%2B+b+%5C+)
и:
Рассмотрим разность
![image](https://tex.z-dn.net/?f=+D+%3D+A+%2B+%5Cfrac%7B1%7D%7BAB%7D+%2B+B+-+%28+A+%2B+%5Cfrac%7B1%7D%7BAb%7D+%2B+b+%29+%3D+%5Cfrac%7B1%7D%7BAB%7D+%2B+B+-+%5Cfrac%7B1%7D%7BAb%7D+-+b+%3D+%5C%5C%5C%5C+%3D+B+-+b+%2B+%5Cfrac%7B1%7D%7BAB%7D+-+%5Cfrac%7B1%7D%7BAb%7D+%3D+B+-+b+%2B+%5Cfrac%7Bb-B%7D%7BABb%7D+%3D+%28+B+-+b+%29+%28+1+-+%5Cfrac%7B1%7D%7BABb%7D+%29+%3E+0+%5C+%2C+)
0 \ , " alt=" D = A + \frac{1}{AB} + B - ( A + \frac{1}{Ab} + b ) = \frac{1}{AB} + B - \frac{1}{Ab} - b = \\\\ = B - b + \frac{1}{AB} - \frac{1}{Ab} = B - b + \frac{b-B}{ABb} = ( B - b ) ( 1 - \frac{1}{ABb} ) > 0 \ , " align="absmiddle" class="latex-formula">
т.к.
![image](https://tex.z-dn.net/?f=+B+-+b+%3E+0+%5C+%2C+%5C+%5C+A+%3E+1+%5C+%2C+)
0 \ , \ \ A > 1 \ , " alt=" B - b > 0 \ , \ \ A > 1 \ , " align="absmiddle" class="latex-formula"> и
![image](https://tex.z-dn.net/?f=+Bb+%3E+1+%5C+.+)
1 \ . " alt=" Bb > 1 \ . " align="absmiddle" class="latex-formula">
Итак:
![image](https://tex.z-dn.net/?f=+D+%3E+0+%5C+%3B+%5C+%5CRightarrow+%5C+G+-+M+%3E+0+%5C+%3B+%5C+%5CRightarrow+%5C+G+%3E+M+%5C+%3B+)
0 \ ; \ \Rightarrow \ G - M > 0 \ ; \ \Rightarrow \ G > M \ ; " alt=" D > 0 \ ; \ \Rightarrow \ G - M > 0 \ ; \ \Rightarrow \ G > M \ ; " align="absmiddle" class="latex-formula"> [ ** 1 ** ]
Рассмотрим разность
![image](https://tex.z-dn.net/?f=+d+%3D+A+%2B+%5Cfrac%7B1%7D%7BAb%7D+%2B+b+-+%28+a+%2B+%5Cfrac%7B1%7D%7Bab%7D+%2B+b+%29+%3D+A+%2B+%5Cfrac%7B1%7D%7BAb%7D+-+a+-+%5Cfrac%7B1%7D%7Bab%7D+%3D+%5C%5C%5C%5C+%3D+A+-+a+%2B+%5Cfrac%7B1%7D%7BAb%7D+-+%5Cfrac%7B1%7D%7Bab%7D+%3D+A+-+a+%2B+%5Cfrac%7Ba-A%7D%7BAab%7D+%3D+%28+A+-+a+%29+%28+1+-+%5Cfrac%7B1%7D%7BAab%7D+%29+%3E+0+%5C+%2C+)
0 \ , " alt=" d = A + \frac{1}{Ab} + b - ( a + \frac{1}{ab} + b ) = A + \frac{1}{Ab} - a - \frac{1}{ab} = \\\\ = A - a + \frac{1}{Ab} - \frac{1}{ab} = A - a + \frac{a-A}{Aab} = ( A - a ) ( 1 - \frac{1}{Aab} ) > 0 \ , " align="absmiddle" class="latex-formula">
т.к.
![image](https://tex.z-dn.net/?f=+A+-+a+%3E+0+%5C+%2C+%5C+%5C+Aa+%3E+1+%5C+)
0 \ , \ \ Aa > 1 \ " alt=" A - a > 0 \ , \ \ Aa > 1 \ " align="absmiddle" class="latex-formula"> и
![image](https://tex.z-dn.net/?f=+b+%3E+1+%5C+.+)
1 \ . " alt=" b > 1 \ . " align="absmiddle" class="latex-formula">
Итак:
![image](https://tex.z-dn.net/?f=+d+%3E+0+%5C+%3B+%5C+%5CRightarrow+%5C+M+-+S+%3E+0+%5C+%3B+%5C+%5CRightarrow+%5C+M+%3E+S+%5C+%3B+)
0 \ ; \ \Rightarrow \ M - S > 0 \ ; \ \Rightarrow \ M > S \ ; " alt=" d > 0 \ ; \ \Rightarrow \ M - S > 0 \ ; \ \Rightarrow \ M > S \ ; " align="absmiddle" class="latex-formula"> [ ** 2 ** ]
![image](https://tex.z-dn.net/?f=+G+-+S+%3D+G+-+M+%2B+M+-+S+%3D+D+%2B+d+%3E+0+%5C+%3B+)
0 \ ; " alt=" G - S = G - M + M - S = D + d > 0 \ ; " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+G+-+S+%3E+0+%5C+%3B+)
0 \ ; " alt=" G - S > 0 \ ; " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+G+%3E+S+%5C+%3B+)
S \ ; " alt=" G > S \ ; " align="absmiddle" class="latex-formula">
Что так же понятно и из сравнения выражений [ ** 1 ** ] и [ ** 2 ** ] :
![image](https://tex.z-dn.net/?f=+G+%3E+M+%3E+S+%5C+%3B+)
M > S \ ; " alt=" G > M > S \ ; " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+A+%2B+%5Cfrac%7B1%7D%7BAB%7D+%2B+B+%3E+a+%2B+%5Cfrac%7B1%7D%7Bab%7D+%2B+b+%5C+%2C+)
a + \frac{1}{ab} + b \ , " alt=" A + \frac{1}{AB} + B > a + \frac{1}{ab} + b \ , " align="absmiddle" class="latex-formula">
что и требовалось выяснить и доказать.